GLOBAL POLICIES AND ETHICAL PERSPECTIVES ON EUTHANASIA: A SYSTEMATIC REVIEW - Bella Wiranti; Arih Diyaning Intiasari; Dwi Sarwani Sri Rejeki (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Background: Euthanasia and assisted dying are increasingly debated worldwide, reflecting tensions between individual autonomy, legal safeguards, and cultural values. Although several countries have legalized euthanasia or medical assistance in dying (MAiD), there are still ethical and policy disagreements. Aims: This study aims to systematically review global policies and ethical perspectives on euthanasia and assisted dying from 2020 to 2025, identifying dominant principles, controversies, and knowledge gaps. Methods: A systematic review was conducted using major databases with keywords including “euthanasia,” “assisted dying,” “global policies,” and “ethical perspectives.” Screening was conducted following the SPIDER and PICOS frameworks, which obtained 9 eligible studies. Subsequently, data were synthesized narratively using thematic analysis. Results: The results showed that most jurisdictions adopted conservative frameworks with strict safeguards, such as eligibility limits and independent assessments. Autonomy and relief of suffering were the most frequent ethical justifications, while sanctity of life, justice, and conscientious objection formed central counterarguments. Furthermore, studies showed tensions, including restrictive criteria undermining autonomy, unequal access shaped by sociocultural factors, and persistent stigma among practitioners. Conclusion: This study shows that euthanasia policies occur in complex intersections of law, ethics, and culture. Based on the results, several recommendations are provided, which include refining safeguards to respect autonomy, enhancing cultural equity, and formalizing conscientious objection. Moreover, further studies should examine complex cases, particularly psychiatric and non-terminal conditions, to strengthen ethical and policy frameworks. Keywords: assisted dying, autonomy, euthanasia, ethics, global policies.